PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT, ASIMETRI INFORMASI, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Nur Ratih Widya Ningrum; Dwi Jaya Kirana; Munasiron Miftah (Universitas Pelita Harapan, 2021)
This study aims to determine the effect of implementing sustainability reports, information asymmetry and financial performance on company value in 36 non-financial companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research is a type of quantitative research using secondary data in the form of annual reports and company sustainability reports. The Fixed Effect Model (FEM) with panel data regression was used in this study using STATA version 16. Based on the results of the test and analysis, it can be concluded that sustainability reports and information asymmetry do not effect firm value, while financial performance has a significant positive effect on firm value and Control variable, namely company size has a significant negative effect on firm value. The results of this study have implications for investors, regulators and future researchers. Policy makers can use these findings, especially on the application of sustainability reports, information asymmetry and financial performance to increase corporate value in Indonesia.Keywords: Sustainability Reporting, Information Asymmetry, financial performance, Firm Size, and Firm Value